2022
DOI: 10.3389/fnut.2022.931313
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Infection: What Have We Learned From the COVID-19 Pandemic

Abstract: ObjectiveThe critical role played by the nutritional status in the complications, duration of hospitalization and mortality in severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection (COVID-19) has emerged from several research studies in diverse populations. Obesity has been associated with an increased risk of serious complications, as the adipose tissue appears to have significant effects on the immune response. The aim of this narrative review was to investigate the relationship between COVI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 79 publications
(73 reference statements)
0
8
0
Order By: Relevance
“…Not surprisingly, a current review of 44 eligible studies from 18 countries around the world has revealed that obesity increases the risk of severe COVID-19 complications, as well as an intensive care need, intubation and mortality rates. In addition, those acute COVID-19 cases with a higher than desirable body mass index appeared more vulnerable to acquiring a COVID-19 infection, as well as experiencing a more severe illness trajectory than the non obese 11 with longer hospital based stays, plus immune system dysfunction or deregulation in cases deemed to present with metabolically 'unhealthy' obesity levels, plus reduced long term COVID-19 vaccine efficacy, and a poorer than desired long term post-COVID health prognosis. [12][13][14] As per Bornstein et al 10 there can thus be no question that it is thus vital to address COVID determinants such as excess body weight that are amenable to improvements or mitigation, at all stages of the disease, and to prevent this health state from worsening during recovery.…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Not surprisingly, a current review of 44 eligible studies from 18 countries around the world has revealed that obesity increases the risk of severe COVID-19 complications, as well as an intensive care need, intubation and mortality rates. In addition, those acute COVID-19 cases with a higher than desirable body mass index appeared more vulnerable to acquiring a COVID-19 infection, as well as experiencing a more severe illness trajectory than the non obese 11 with longer hospital based stays, plus immune system dysfunction or deregulation in cases deemed to present with metabolically 'unhealthy' obesity levels, plus reduced long term COVID-19 vaccine efficacy, and a poorer than desired long term post-COVID health prognosis. [12][13][14] As per Bornstein et al 10 there can thus be no question that it is thus vital to address COVID determinants such as excess body weight that are amenable to improvements or mitigation, at all stages of the disease, and to prevent this health state from worsening during recovery.…”
Section: Search Resultsmentioning
confidence: 99%
“…Indeed, in the face of no welldefined medical model for managing long COVID, or preventing acute COVID, older adults who are vulnerable to being overweight or are already obese may be assisted in their recovery to optimal wellbeing via a combination of physical activity approaches as well as efforts to optimize mental health. 11 As outlined by Feng et al 6 while not well studied in the West, Qigong and its many variants are exercises that have been used to promote health for more than 5000 years with generally favourable results relevant to long COVID recovery in particular, as well as secondary COVID infections. This ancient component of traditional Chinese Medicine, 15,16 which involves a series of breathing exercises, 17 as well as meditation, and gentle body movements to achieve its aims, 15 and is designed to help the individual to relax the mind and level of excess stress, 18 thus setting the stage for intrinsic healing opportunities and possibly diminishing any prevailing inflammatory responses, 19 and feelings of psychological distress may be of immense benefit in consideration of the fatigue, 'brain fog' symptoms, breathing challenges, and pain that are found in long COVID cases and that are hard to treat in the medical model alone.…”
Section: Search Resultsmentioning
confidence: 99%
“…Endocrine system is also affected by COVID-19, including pancreas, adrenal, testicle, reproductive tract, parathyroid gland and the thyroid gland ( 9 14 ) ( Figure 1 ). Moreover, endocrine-metabolic disturbances, such as diabetes mellitus and obesity, are highly associated to severe illness ( 15 , 16 ).…”
Section: Covid-19 and Thyroid Gland: General Conceptsmentioning
confidence: 99%
“…Available data suggest that COVID-19 progression is dependent on metabolic mechanisms 1 . Individuals with COVID-19 who developed acute respiratory distress syndrome and death are characterized by older age and a higher prevalence of hypertension, obesity, diabetes and cardiovascular diseases compared to individuals with milder disease [1][2][3][4][5][6] . Hyperglycaemia and hyperlipidaemia are also risk factors for acute respiratory distress in patients with COVID-19 disease 1,7 .…”
mentioning
confidence: 99%
“…Systolic blood pressure, mm Hg 123 (16) 123 (16) 123 (16) Diastolic blood pressure, mm Hg 76 (31) 76 (31) 76 (30) Heart rate, beats per minute 82 (13) 82 (14) 82 (12) BMI, kg/m 2 28 (6) 28 ( 6) 28 (6) eGFR, ml min −1 per 1.73 m 2 101 (20) 101 (21) 100 (20) Leucocyte count, 10 Results are presented as number (proportion) for binary or categorical variables and mean (standard deviation) for continuous variables. Proportions were calculated using the number of individuals with the characteristic divided by the number of participants with non-missing data about the characteristic.…”
mentioning
confidence: 99%